2022
DOI: 10.3390/jcm11154599
|View full text |Cite
|
Sign up to set email alerts
|

I-FABP as a Potential Marker for Intestinal Barrier Loss in Porcine Polytrauma

Abstract: Polytrauma and concomitant hemorrhagic shock can lead to intestinal damage and subsequent multiple organ dysfunction syndrome. The intestinal fatty acid-binding protein (I-FABP) is expressed in the intestine and appears quickly in the circulation after intestinal epithelial cell damage. This porcine animal study investigates the I-FABP dynamics in plasma and urine after polytrauma. Furthermore, it evaluates to what extent I-FABP can also act as a marker of intestinal damage in a porcine polytrauma model. Eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…We are aware that DAO is a highly reactive intracellular enzyme in the cytoplasm of human and all mammalian intestinal mucosal cells, and when intestinal mucosal cells are impaired and necrotic, DAO is released into the blood, leading to increased blood activity, so blood DAO levels are a good indicator for monitoring intestinal mucosal injury [ 35 ]. I-FABP is a protein expressed only by enterocytes, which is released into the circulation after enterocyte injury and has been demonstrated to be a promising marker for early identification of intestinal ischemia and injury, all of which are consistent with the results of our study, suggesting that SAL possesses a beneficial therapeutic effect on intestinal IR injury [ 36 ].…”
Section: Discussionsupporting
confidence: 89%
“…We are aware that DAO is a highly reactive intracellular enzyme in the cytoplasm of human and all mammalian intestinal mucosal cells, and when intestinal mucosal cells are impaired and necrotic, DAO is released into the blood, leading to increased blood activity, so blood DAO levels are a good indicator for monitoring intestinal mucosal injury [ 35 ]. I-FABP is a protein expressed only by enterocytes, which is released into the circulation after enterocyte injury and has been demonstrated to be a promising marker for early identification of intestinal ischemia and injury, all of which are consistent with the results of our study, suggesting that SAL possesses a beneficial therapeutic effect on intestinal IR injury [ 36 ].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, serum I-FABP levels could theoretically be used as a specific marker for detecting NEC. 34 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, serum I-FABP levels could theoretically be used as a specific marker for detecting NEC. 34,35 Using I-FABP ablation, Lackey et al 36 observed increased enterocyte mortality in the experimental mouse group with a shortened villus length, thinner myometrial layer, and decreased goblet cell density. Wang et al 37 studied the importance of I-FABP by evaluating intestinal barrier dysfunction during the early stage of severe burns in 36 mice, which were randomly divided into healthy control and scalded groups.…”
Section: Discussionmentioning
confidence: 99%
“…DAO, a highly reactive intracellular enzyme, and i-FABP, a soluble protein, are both located in the upper small intestinal mucosal villi in mammals. Zonulin is the sole known physiological regulatory protein for intestinal permeability [ 52 , 53 , 54 ]. When the intestinal permeability increases due to the stimulation of bacteria and antigens, DAO, i-FABP, and zonulin are secreted into the enteric cavity and subsequently into the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…When the intestinal permeability increases due to the stimulation of bacteria and antigens, DAO, i-FABP, and zonulin are secreted into the enteric cavity and subsequently into the bloodstream. Therefore, the concentrations of DAO, zonulin, and i-FABP in serum can reflect the integrity of and the degree of damage to the intestinal mechanical barrier [ 52 , 53 , 54 ]. In this study, dietary S. cerevisiae significantly decreased the serum levels of LPS and zonulin in the aged dogs, suggesting that S. cerevisiae could improve the intestinal barrier function and potentially maintain gut health in aged dogs.…”
Section: Discussionmentioning
confidence: 99%